Rediseño del sistema de Agua Potable, estudio y Diseño del Alcantarillado sanitario y pluvial para las comunidades de la victoria y santa cruz pertenecientes a la parroquia barbones del Cantón el Guabo, Provincia de el Oro - Espinoza Arias, Victor Manuel (2015)
The insufficient supply of drinking water, and lack of sanitary and storm sewers, is the main problem for health and good living of people , helping environmental contamincaion it generates in comunicadades victory and Santa Cruz , belonging the Bourbons parish of El Guabo Canton province of El Oro. therefore this project aims primarily to develop the redesign of the drinking water system , study and design of sanitary and storm sewer for the communities of Victoria and Santa Cruz .